An endogenous basis for synchronisation characteristics of the circadian rhythm in proliferating Lemna minor plants. Issue 5 (30th December 2021) - Ueno, Kenya; Ito, Shogo; Oyama, Tokitaka
Summary: The circadian clock is a cell‐autonomous system that functions through the coordination of time information in the plant body. Synchronisation of cellular clocks is based on coordination mechanisms; the synchronisation characteristics of proliferating plants remain unclear. The bioluminescence circadian rhythms of fronds (leaf‐like plant units) of proliferating Lemna minor plants carrying a circadian bioluminescence reporter, AtCCA1:LUC, were spatiotemporally analysed at a cell‐level resolution. We focused on spontaneous circadian organisation under constant light conditions for plants with light : dark treatment (LD grown) or without it (LL grown). Fronds developing even from an LL‐grown parental frond showed coherent circadian rhythms among them. This allowed the maintenance of circadian rhythmicity in proliferating plants. Inside a frond, a centrifugal phase/period pattern was observed in LD‐grown plants, whereas various phase patterns with travelling waves were formed in LL‐grown plants. These patterns were model simulated by local coupling of heterogeneous cellular circadian oscillators with different initial synchronous states in fronds. Spatiotemporal analysis of the circadian rhythms in proliferating plants reveals spontaneous synchronisation manners that are associated with local cell–cell coupling, spatial phase patterns and developmental stages.